Hipoclorito de sodio como método para la desproteinización del esmalte en la adhesión para ortodoncia fija. Revisión bibliográfica - Valle Lozada, Byron Sebastián (2025)
Employing an appropriate method to improve the adhesion strength of fixed orthodontic appliances to the enamel surface is a crucial step in ensuring the success of orthodontic treatment. Objective: To evaluate the effectiveness of sodium hypochlorite as a method of enamel deproteinization in adhesion for fixed orthodontics and its impact on the quality of orthodontic treatment. Materials and methods: A search was carried out in different databases such as EBSCO and PUBMED using PRISMA parameters to compile the included studies. Results: 60 scientific articles were collected, of which 10 significant articles for the research were included through a selection process. For the data obtained, a descriptive analysis was carried out that included means, standard deviation of the Shear Bond Strength (SBS) values. Conclusion: Deproteinization with 5.25% NaOCl and papain gel provided a significant increase in SBS. This efficiency was lower when compared to conventional etching, providing greater SBS and adhesive penetration into the enamel surface. Furthermore, deproteinization of enamel with sodium hypochlorite in 5.25% concentration showed a significant increase in adhesion strength compared to 5%, but no difference was found.